Scope of mobile health in Indian health care system – the way forward - Ahamed, Farhad; Palepu, Sarika; Dubey, Mahasweta; Nongkynrih, Baridalyne (International Journal Of Community Medicine And Public Health, 2017)
India is currently undergoing increased urbanisation and population growth. The existing health care facilities and health care personnel are not able to cater to the health care needs of the population. Hence, a demand-supply gap is prevailing in the country. Improper functioning of three tier health care delivery, inaccessibility of secondary and tertiary government health services are the other major hurdles in effective health care utilisation. Technological interventions like tele-consultation strived continuously to tackle this crisis but had attained limited success. Other technological advancements as mobile based interventions (mHealth) have been emerging in the recent times. mHealth includes the use of telecommunication and multimedia technologies integrated with mobile and wireless healthcare delivery system. With success stories round the globe, it can be marked that mobile technology in the present scenario has gained substantial effects on health outcomes. Using mobile technology offers a tremendous opportunity for developing countries as India to advance in health care delivery by effectively utilising scarce resources. The vastly underserved healthcare market combined with high mobile phone penetration and rapidly growing smart phone adoption creates enabling environment condition for mHealth adoption in India. mHealth, being user friendly and cost effective, would be an interesting initiative in developing world. Customised application and sustainable financial models which could suit the existing local healthcare delivery networks would yield beneficial outcomes.